Analysis of Student's Creative Thinking Ability on Arithmetic Sequences in the Lesson Study Framework - Rayinda Aseti Prafianti; Novitasari Novitasari; M Ulul Albab; Dian Novi Ambarwati (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This research aims to determine the creative thinking ability of students in arranging and solving contextual problems on arithmetic sequence. This research is a descriptive quantitative study through a Lesson Study framework with a subject of 18 students of the Mathematics Education study program at the Islamic University of Lamongan. The instruments in this study include attitude assessment sheets used to measure student activity in participating in learning and Student Worksheets used to measure students' creative thinking ability in arranging and solving contextual problems on arithmetic sequences. The results of the analysis show that the average score of student activities during learning is 85.13% while the average score of students' creative thinking ability is 71.875% in the Enough category.